2008
DOI: 10.1103/physrevd.78.124022
|View full text |Cite
|
Sign up to set email alerts
|

Three-qubit operators, the split Cayley hexagon of order two, and black holes

Abstract: The set of 63 real generalized Pauli matrices of three-qubits can be factored into two subsets of 35 symmetric and 28 antisymmetric elements. This splitting is shown to be completely embodied in the properties of the Fano plane; the elements of the former set being in a bijective correspondence with the 7 points, 7 lines and 21 flags, whereas those of the latter set having their counterparts in 28 anti-flags of the plane. This representation naturally extends to the one in terms of the split Cayley hexagon of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 44 publications
(125 reference statements)
1
102
0
Order By: Relevance
“…In the apparently separate world of quantum gravity, the Bekenstein-Hawking entropy [1,2] of black holes has also occupied centre stage. Despite their apparent differences, recent work [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17] has demonstrated a correspondence between the two. Although we still do not know whether there are any physical reasons underlying these mathematical coincidences, there is now a growing dictionary, which translates a variety of phenomena in one language to those in the other.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the apparently separate world of quantum gravity, the Bekenstein-Hawking entropy [1,2] of black holes has also occupied centre stage. Despite their apparent differences, recent work [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17] has demonstrated a correspondence between the two. Although we still do not know whether there are any physical reasons underlying these mathematical coincidences, there is now a growing dictionary, which translates a variety of phenomena in one language to those in the other.…”
Section: Overviewmentioning
confidence: 99%
“…In [16] the P SL(2, F 7 ) symmetry of the N = 8 black hole entropy has been related, via a special set of 63 three-qubit operators, to the generalised hexagon of order two using the dictionary constructed in section 10.2.1. They further suggested that the full G 2 (2) symmetry of the hexagon may be preserved by the black hole entropy.…”
Section: D3 Decomposition Of the 56-dimensional Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…This research † † The representation found for the group A 2 (2) is different from [48]. The generators x 1 and x 2 contain the Pauli spin matrices and satisfy x…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In particular, the P SL 2 (7) subgroup of the automorphism group of the hexagon and its associated Coxeter subgeometry were found to be intricately related to the E 7 -symmetric black-hole entropy formula in string theory, given a prominent role played by Veldkamp points that answer to Klein quadrics in the ambient projective space PG(5, 2) [7]. On the other hand, the E 6 -symmetric entropy formula describing black holes and black strings in five dimensions is underlaid by the geometry of generalized quadrangle GQ (2,4) and its Veldkamp space [8]; here, the two pronounced truncations of the entropy formula with 15 and 11 charges correspond exactly to two distinct types of Veldkamp points of GQ(2, 4) [9].…”
Section: Introductionmentioning
confidence: 99%